OPTIMASI PENJUALAN SIOMAY BATAGOR SURYA MENGGUNAKAN PEMROGRAMAN LINEAR DAN METODE GRAFIK - Angelia; Evan Ivander; Kristina Yuliana Julaan; Rossi Melanie; Stevani; Dudy Effendy (Andromeda : Jurnal Manajemen dan Bisnis Syariah, 2026)
Abstract The "Siomay and Batagor Surya" business is a type of micro, small, and medium enterprise (MSME) in the culinary sector with high demand. However, business actors face challenges in determining the most efficient production combination due to limited resources, such as production time and raw materials. This study aims to determine the production combination that can generate the highest sales using a linear programming method through a graphical approach. This study uses a descriptive quantitative method and collects data through direct interviews with business owners regarding production time, raw material capacity, and product selling prices. The data is then analyzed using the objective function and constraint function in a linear programming framework. From the graphical method analysis, the optimal solution is obtained at point (0.72), which is to produce 72 units of batagor and not produce siomay. This production combination generated the highest daily sales of Rp720,000.00. The findings of this study indicate that linear programming techniques can help MSMEs make more effective and efficient production decisions based on data.